Degradation of the mixture of ethyl formate, propionic aldehyde, and acetone by Aeromonas salmonicida: A novel microorganism screened from biomass generated in the citric acid fermentation industry. (November 2020) - Yao, Xiaolong; Wang, Ke; Zhang, Shanshan; Liang, Shan; Li, Ke; Wang, Chun; Zhang, Tingting; Li, Hailong; Wang, Juncheng; Dong, Liming; Yao, Zhiliang
Abstract: Microorganisms play important roles in the degradation of volatile organic compounds. Aeromonas salmonicida strain (AEP-3) generated from biomass in the citric acid fermentation industry was screened and subjected to denaturing gradient gel electrophoresis (DGGE) fingerprinting and 16S rDNA gene sequencing. The growth conditions of AEP-3 in Luria–Bertani broth were optimized at 25 °C and approximately pH 7. AEP-3 was used to degrade ethyl formate, propionic aldehyde, or acetone alone and their mixture. The concentrations of ethyl formate, propionic aldehyde, and acetone were below 7500, 600, and 800 mg L −1, respectively, and their maximum degradation efficiencies were 100%, 92.41%, and 34.75%. AEP-3 first degraded acetone and propionic aldehyde in the mixture, followed by ethyl formate. The degradation pathways of these organic compounds in the mixture and their substrate interactions during degradation were explored. Propionic aldehyde was first converted into propionic acid in the metabolic process and was involved in the subsequent carboxylic acid cycle. By contrast, ethyl formate was first hydrolyzed into formic acid and ethanol. Then, formic acid participated in the cyclic metabolism of carboxylic acid, whereas, ethanol was hydrolyzed into acetaldehyde and acetic acid through alcohol and aldehyde dehydrogenase. Additionally, acetone directly interacted with nitrate in the medium under the action of hydrogen ions and produced carbon dioxide, water, and nitrogen. Overall, this study provides a new degrading bacterium biodegradability toward the exhaust gas of citric acid fermentation. Graphical abstract: Image 1 Highlights: Biodegradation of VOCs in the exhaust gas of citric acid fermentation. Role of Aeromonas salmonicida strain in degradation of VOCs was evaluated. Degradation pathways of the three VOCs in the mixture were explored. The study provided a newly degrading bacterium with biodegradability towards VOCs.